Impacto económico de la variabilidad climática en la producción - Quirolo, Maria Eugenia; Pellerano, Liliana Laura; Gesualdo, Etelvina Angelica; Rosello Brajovich, José Emilio (INTA, 2022)
Presentación en diapositivas